1991
DOI: 10.1111/j.1476-5381.1991.tb12122.x
|View full text |Cite
|
Sign up to set email alerts
|

Antipyretic actions of human recombinant lipocortin‐1

Abstract: The effect of human recombinant lipocortin-1 (hrLC-1) on the pyrogenic actions of the synthetic polyribonucleotide polyinosinic: polycytidylic acid (poly I: C) has been studied in conscious rabbits. Poly I: C (2.5 pg kg-) given i.v. produced a biphasic fever with a first peak after 90-105 min and a second peak between 225-240 min. hrLC-1 (50ougkg-) given i.v. simultaneously with the poly I: C produced a significant reduction in the febrile response but without complete suppression. The thermal response index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
2

Year Published

1993
1993
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 8 publications
(7 reference statements)
0
35
1
2
Order By: Relevance
“…This pool of lipocortin is significant as Carnuccio et al (1981) and Cirino & Flower (1987b) reported that it is the external membrane-associated lipocortin 1 that produces its biological effects. Furthermore, the models in which lipocortin 1 has been shown to have biological activity are those in which the protein has been applied externally (Cirino & Flower, 1987a;Cirino et al, 1987;Davidson et al, 1991 (Sheets et al, 1987) and in porcine heart (Pula et al, 1990) and A431 cells (Ando et al, 1991). In the first two examples, lipocortin 1, and 5 and 6 respectively could be extracted by non-ionic detergents but not by EGTA, and hence resemble the membrane-bound pools observed in elicited cells.…”
Section: Discussionmentioning
confidence: 99%
“…This pool of lipocortin is significant as Carnuccio et al (1981) and Cirino & Flower (1987b) reported that it is the external membrane-associated lipocortin 1 that produces its biological effects. Furthermore, the models in which lipocortin 1 has been shown to have biological activity are those in which the protein has been applied externally (Cirino & Flower, 1987a;Cirino et al, 1987;Davidson et al, 1991 (Sheets et al, 1987) and in porcine heart (Pula et al, 1990) and A431 cells (Ando et al, 1991). In the first two examples, lipocortin 1, and 5 and 6 respectively could be extracted by non-ionic detergents but not by EGTA, and hence resemble the membrane-bound pools observed in elicited cells.…”
Section: Discussionmentioning
confidence: 99%
“…This indeed is congruent with other evidence. For example the external application of lipocortin to cells or its intravenous administration to animals (Cirino et al, 1989;Carey et al, 1990;Davidson et al, 1991) produces a prompt and dramatic effect on eicosanoid generation, inflammation or fever. Furthermore, the existence of a protein binding site with a high affinity for lipocortin has been detected on the surface of some human cells with the obvious implication that this is a receptor or a target enzyme (Goulding et al, 1990b).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of purified human recombinant lipocortin 1 produces anti-inflammatory and antipyretic effects in rats and rabbits (Cirino et al, 1989;Carey et al, 1990;Davidson et al, 1991), eicosanoid suppressive actions in cells in vitro and ameliorates ischaemic damage (infarct size and cerebral oedema) produced in rat brain by occlusion of the middle cerebral artery (Relton et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Annexin 1 is a glucocorticoid-inducible protein (14) that mediates many of the anti-inflammatory actions of glucocorticoids in models of acute (15) and chronic (16) inflammation including modulation of leukocyte trafficking (17,18), ischemic damage (19), pain (20), and fever (21). Evidence for a functional link between annexin 1 and apoptosis has emerged (22,23).…”
Section: T Is Increasingly Appreciated That Macrophage (M)mentioning
confidence: 99%
“…As discussed above, annexin 1 protein is up-regulated by glucocorticoids to mediate some of their anti-inflammatory properties (15)(16)(17)(18)(19)(20)(21). We investigated the potential role of endogenous annexin 1 on phagocytosis of apoptotic cells by M. Human monocytes were cultured for 5 days in the presence or absence of 1 M Dex.…”
Section: Supernatants From Dex-treated M Contain Annexin 1 and Are Asmentioning
confidence: 99%